Polarisasi Cahaya dan Penentuan Nilai Indeks Bias dengan Metode Brewster Angle - istiqomah nugraheny; Wahyu Nurfauzi; Devara Ega Fausta; S Supurwoko; Rengga Ngesthi Pambuka (Jurnal Fisika dan Aplikasinya, 2018)
An experiment for determine brewster angle and study polarization from reflected light has been done. Equipment which requested for this experiment are a spectrophotometry table as the place the sample and read the reflected angle, photodetector as recording instrument to determine value of intensity from reflected light, resin as tested sample, He-Ne Laser as main light resource, and a polarizer used as light polarizator. The result from this experiment shown there are 2 mode from polarized light, TE mode and TM mode. Mode which used to determine the brewster angle is TM Mode. The value of  brewster angle from resin sample on this experiment is 52,5o. The value from refractive index is (1,303 ± 0,055) compared by the literature which has been used is (1,46±0,01).